Parenting the crisis : the cultural politics of parent-blame - Jensen, Tracey (Policy Press, 2018)
This book examines how pathologising ideas of failing, chaotic and dysfunctional families create a powerful consensus that Britain is in the grip of a 'parent crisis' and are used to justify increasingly punitive state policies.